“Investment management” – A study on Social Islami Bank Limited, Baryarhat branch, Chittagong - Rahaman, Saifur (BRAC University, 2016)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Master of Business Administration, 2016.